2010
DOI: 10.1007/s00330-010-1998-x
|View full text |Cite
|
Sign up to set email alerts
|

Staging of uterine cervical cancer with MRI: guidelines of the European Society of Urogenital Radiology

Abstract: Objective: To design clear guidelines for the staging and follow-up of patients with uterine cervical cancer, and to provide the radiologist with a framework for use in multidisciplinary conferences. Methods: Guidelines for uterine cervical cancer staging and follow-up were defined by the female imaging subcommittee of the ESUR (European Society of Urogenital Radiology) based on the expert consensus of imaging protocols of 11 leading institutions and a critical review of the literature. Results: The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
208
2
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(231 citation statements)
references
References 41 publications
4
208
2
17
Order By: Relevance
“…In existing guidelines for the N-staging of CC, different studies have made various suggestions regarding the use of PET, PET/CT and MRI (20,21). The Information Centre for Standards in Oncology of the German Cancer Society recommended neither PET/CT nor MRI for N-staging in CC patients, although they recommend the use of PET or ultrasound scanning for N-staging in specific cases (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In existing guidelines for the N-staging of CC, different studies have made various suggestions regarding the use of PET, PET/CT and MRI (20,21). The Information Centre for Standards in Oncology of the German Cancer Society recommended neither PET/CT nor MRI for N-staging in CC patients, although they recommend the use of PET or ultrasound scanning for N-staging in specific cases (20).…”
Section: Discussionmentioning
confidence: 99%
“…The Information Centre for Standards in Oncology of the German Cancer Society recommended neither PET/CT nor MRI for N-staging in CC patients, although they recommend the use of PET or ultrasound scanning for N-staging in specific cases (20). The European Society of Urogenital Radiology suggested that lymph node detection should be performed with axial T1-weighted sequences (MRI) to assess suspicious pelvic and abdominal lymph nodes, as well as the intravenous administration of gadolinium-chelate for lesions <2 cm (21). The variety of different guidelines reflects the discussions and controversies regarding the optimum method for the N-staging of CC.…”
Section: Discussionmentioning
confidence: 99%
“…MR imaging can influence the treatment protocol, and be used to identify important prognostic factors such as tumor volume, status of parametrium, pelvic side wall invasion, presence of metastatic lymphadenopathy, and spread to local and distant organs, thus aiding to determine palliative MR examination (21). MR appearance after hysterectomy includes absence of the uterus, formation of the vaginal fornix by a linear soft tissue configuration, and normal vaginal wall with a smooth, low signal intensity muscular wall on T2-weighted MR images (Fig.…”
Section: Mr Evaluation Of Tumor Response To Treatmentmentioning
confidence: 99%
“…Accordingly, DCE MRI should not be part of the routine MRI protocol of cervical carcinoma, and its use should only be limited to specific occasions; small tumors not seen on T2W images and in post-treatment follow up [47], as recommended by the European Society of Urogenital Radiology (ESUR) guidelines for staging cervical carcinomas [24,34,36]. Other studies suggest that DCE MRI also has a role is determining the exact endocervical extent of the tumor as well as differentiating between cervical and endometrial carcinomas [34].…”
Section: Cervical Tumor Detectionmentioning
confidence: 99%